ETHYL ACETATE FRACTION OF HIBISCUS SABDARIFFA L. (MALVACEAE) ENHANCE LACTOGENIC ACTIVITY AND DOWN REGULATE OXYTOCIN RECEPTOR MRNA GENE EXPRESSION IN RAT MAMMARY GLAND (FUDMA JOURNAL OF SCIENCES, 2025)
In under developed countries some local people traditionally use herbs to boost milk production or induction of lactation than the antipsychotic drugs that have serious side effects like drowsiness and depression. The objective of this study was to determine molecular pathway for mRNA gene expression of Oxytocin receptor (OTR) in lactogenic effect of Hibiscus sabdariffa L. Fifteen lactating Wistar rats grouped into five (n=5), control group received 1 ml/kg of distilled water, metoclopramide group received 5 mg/kg and ethyl acetate fraction of Hibiscus sabdariffa L group received 800 mg/kg for 14 days. Serum, milk production, milk yield, mammary gland and pup weight (daily) were collected for analysis. Results showed that the ethyl acetate fraction of Hibiscus sabdariffa L. increased significantly (p
Keywords: Milk; Lactation; Oxytocin; mRNA; Expression; Hibiscus; Sabdariffa